Critical Thinking Skills in Performance-Based Assessment: Instrument Development and Validation - Adri, Junil; Refdinal; Ambiyar; Abdullah, Arman Shah (Journal of Technical Education and Training, 2022)
The purpose of this study is to produce a performance-based assessment instrument to stimulate students’ critical thinking in welding quality testing courses. The ability to think critically occurs when you understand the material given. Performance-based assessment can be done on the process and learning outcomes. The method used in this study is the Borg and Gall method with ten steps of development. The practice of welding quality testing has an analysis orientation that results in an acceptance decision on the welding quality. The results are validated in terms of content, language, and constructs by specified experts. The results of the performance-based assessment design use five stages, namely: determining the underlying problem, creating an assessment context, determining the assessment rubric, carrying out a performance assessment, and formulating the assessment results, and responding to the evaluation results. The rubric used is a rubric with a scoring form. The instrument design is following the task of the inspection of welding results. The output of welding quality testing learning is a report containing observations results and making decisions on welding quality based on critical thinking skills. The performance-based assessment provides independence in making decisions. Performance-based assessment is suitable for practical learning that collaborates with motoric movements and knowledge.